Vous êtes sur la page 1sur 5

E e e e = e (E, )

E e x e e = e e x = x e = x x x x = e (E, )

y e e = e e x = x e = x e y = y e y x x = x x x = y x y y x e x x = y x y = y x = e y y = x

 ∗ e x y z e e x y z x x y z e y y z e x z z e x y ∗ e x y z e e x y z x x e z y y y z e x z z y x e

x y z

U n n U z n = 1 |z| n = 1 |z| = 1 R + x n = 1 U n

1 U n z n = z n = 1 (zz ) n = z n z n = 1

z n = 1

1 n = 1 U

z

0 x

x y = 0 y = x 1 1 R\{1}

(R, +) x

1 (x y) = (1 x)(1 y) x x ∗ · · · ∗ x 1 x x ∗ · · · ∗ x = (1 x) n x x ∗ · · · ∗ x = 1 (1 x) n

(y z) = (x y) z = x + y + z xy xz yz + xyz

x

1 x

x xy + y + + xz z + + yz xyz 0 x

x

1

(x

xy < 1

th : R ] 1; 1[ th (x + y) = th (x) th (y)

1 <

x (y x) =

(x y) z =

] 1; 1[ x

1)(y 1) = xy x y 1 < 0 (1 + xy) < x + y x + y

<

1

y

<

1 + xy x + y

1 +

1 +

xy 1 < x 1 < y

 ◦ f 1 f 2 f 3 f 4 f 5 f 6 f 1 f 1 f 2 f 3 f 4 f 5 f 6 f 2 f 2 f 6 f 4 f 5 f 3 f 1 f 3 f 3 f 5 f 1 f 6 f 2 f 4 f 4 f 4 f 3 f 2 f 1 f 6 f 5 f 5 f 5 f 4 f 6 f 2 f 1 f 3 f 6 f 6 f 1 f 5 f 3 f 4 f 2

G f 1 f 1 f 2 f 2 f 2 = f 6 {f 1 ; f 2 ; f 6 } G f 4 f 5 f 6 f 1 f 2 {f 1 ; f 3 } G G {f 1 ; f 4 } {f 1 ; f 5 } G

x, y R

{−1; 1} R

+

x y

|x| ×

|y| =

|xy| xy

θ

2πZ = {2| k Z}

e iθ e i(θ+θ ) = e iθ e iθ U

axa 1 aya 1 = a(xy)a 1 axa 1 = e ax = a x = e y a 1 ya y a 1 ya

H 1 H 2 H 1 H 2 H 1 H 2 x y H 1 H 2 x y H 1 H 2 H 1 H 2 G

C G = {x G | ∀y G, xy = yx} =

yG C y

C y = {x G | xy = yx} C y C G

x y E (xy) 1 = xy (xy) 1 = y 1 x 1 yx

x y) z = x (y z) = x + y + z 2 1 x x 2 R\{1}

Z[i 2] 0 1 C

1 (u n ) (u n )

m u n M n M u n m

1

+

E

A P(E) AA = (A\A) (A\A) = A E B E

A B = E A = B = E

A B = ∅ ⇒ A = B =

A A

(P(F ), , )

E

2 3

2 × 2 = 2 3 6 3 2 = 1

a + b 2 + c 3 + d 6 (a, b, c, d) R 4 K K 0 1

2 × 6 = 2 3 3 × 6 = 3 2

R K a + b 2 + c 3 + d 6

a + b 2 + c 3 + d 6 aa + 2bb + 3cc + 4dd = 1 ab + ba + 3cd + 3dc = 0

ac + ca + 2bd + 2db = 0 ad + da + cb + bc = 0 (a, b, c, d)

(x 3)(y 2) = 6 6 8 6 × 1 3 × 2 2 × 3 1 × 6 {(9, 3); (6, 4); (5, 5); (4, 8); (2, 4); (1, 1); (0, 0); (3, 1)}

x

1

1

1

3

y

z x 4

x = 3

1

1

x + y +

4

1

z 1 x = y = z = 3

x + y + z

1

1

1

z > 1 y = 3

y = 4 (2, 3, 6) (2, 4, 4) y 5 x = 1 1 1 1 x = 1 y = z y x = 1 y = z = 1 {(2; 3; 6); (2; 4; 4); (3; 3; 3); (1; y; y) | y N }

x = 2 y = 2

x + y +